Prevalence of depression among married women in a rural area of North Kerala: A cross-sectional study - K K Lamiya; Sheela P Haveri; Jesha Mohammedali Mundodan (Wolters Kluwer Medknow Publications, 2023)
Depression is a common illness, it being the fourth-leading cause of disability in the world. The global lifetime prevalence falls between 8% and 12%, with female preponderance. A cross-sectional study was designed to assess the burden of depression among married women in a rural setting in North Kerala and identify its sociodemographic risk factors. The sample size was calculated to be 453 (prevalence = 24.9%; error = 20%; design-effect = 1.5). Systematic random sampling was used to select the participants from the eligible couple register. They were interviewed using MINI and Montgomery-Ashberg Depression Rating Scales. Descriptive analysis showed that 24.2% was suffering from current depression, mostly mild and none severe. Two percent reported past depression and 5.4% experienced spousal violence. Poor family support, experience of domestic violence, morbidity, and older spouses were found to be significant risk factors. The provision of mental health services by trained personnel and strict vigilance against the marriage of girls below the legal age and domestic violence are need of the hour.